Marine Group II Dominates Planktonic Archaea in Water Column of the Northeastern South China Sea - Liu, Haodong; Zhang, Chuanlun L.; Yang, Chunyan; Chen, Songze; Cao, Zhiwei; Zhang, Zhiwei; Tian, Jiwei (Frontiers in Microbiology, 2017)
Temperature, nutrients and salinity are among the important factors constraining the distribution and abundance of microorganisms in the ocean. Marine Group II (MGII) belonging to Euryarhaeota commonly dominates the planktonic archaeal community in shallow water and Marine Group I (MGI, now is called Thaumarchaeota) in deeper water in global oceans. Results of quantitative PCR (qPCR) and 454 sequencing in our study, however, showed the dominance of MGII in planktonic archaea throughout the water column of the northeastern South China Sea (SCS) that is characterized by strong water mixing. The abundance of ammonia-oxidizing archaea (AOA) representing the main group of Thaumarchaeota in deeper water in the northeastern SCS was significantly lower than in other oceanic regions. Phylogenetic analysis showed that the top operational taxonomic units (OTUs) of the MGII occurring predominantly below 200 m depth may be unique in the northeastern SCS based on the observation that they are distantly related to known sequences (identity ranging from 90%-94%). The abundance of MGII was also significantly correlated with total bacteria in the whole column, which may indicate that MGII and bacteria may have similar physiological or biochemical properties or responses to environmental variation. This study provides valuable information about the dominance of MGII over ammonia-oxidizing archaea in both shallow and deep water in the northeastern SCS and highlights the need for comprehensive studies integrating physical, chemical and microbial oceanography.